CURRENT TRENDS IN THE FIELDS OF GEODESY, LAND MANAGEMENT, LAND CADASTRE AND URBAN PLANNING: Array - Pilicheva, M.; Anopriienko, T. (Municipal economy of cities. Series: «Economy science», 2021)
The article is devoted to the study of changes in geodesy, land management, State land cadastre and urban planning. It is proved that changes in certain areas are related to changes in the main directions of land reform in Ukraine, namely the formation of territorial communities and the introduction of a full and open land market. The process of formation of communal property in Ukraine and formation of territorial communities are investigated. At the same time, a special type of documentation appears – a comprehensive plan of spatial development of territorial communities, which is both land management documentation and urban planning documentation at the local level and includes topographic and geodetic data. To determine the boundaries of the territory of the community, a new type of land management documentation was introduced – a land management project to establish the boundaries of the territory of the territorial community. It is established that the number and area of territorial communities are different and can differ dozens of times. It is determined that the issue of creating geospatial data infrastructure is becoming more and more developed in Ukraine, because it combines data from the State Geodetic Network, information from the State Land and Urban Cadastre, which provides additional amplification and data entry, development of documentation using its current data. The issue of land market regulation is considered. Its subjects and features of acquisition of the property right to land plots of agricultural purpose are defined. The maximum size of the total area of agricultural land plots is presented – no more than ten thousand hectares, but until January 1, 2024 for the citizens of Ukraine this value should not exceed 100 hectares. The tendency of changes in establishing the sale price of the land plot, namely in carrying out the normative monetary assessment is determined. It is proposed to create a single assessment procedure for all land plots, regardless of their purpose, but taking into account the boundaries of the territorial community. The average cost of agricultural land by regions of Ukraine is analyzed. It is determined that it is uneven and can differ by 2-2.5 times. It is established that the introduction of real-time electronic auctions for the purchase and sale of agricultural land of all forms of ownership allows to achieve openness and transparency of the land market, as well as attracting a wider range of potential buyers.